5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2
if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7
x2 + 2x -6 = 0 x2 + 2x + 1 = 7 (x + 1)2 = 7 x = -1 ± √7
2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9
(4 + 2x) - (-2x + 1) = 13 + 6 4 + 2x + 2x -1 = 19 4x +3 = 19 4x = 19 - 3 4x = 16 therefore x = 16/4 x = 4
x=1
5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2
6y
2x + 1 = 13; 2x = 12; x = 6
if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7
6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1
2x+1=6 -1 -12x=5/2 /2x=2.5 or 2 1/2
4+2x-2x+1=13+6 Combine like terms. (4+1=5; 2x-2x=0; 13+6=19) 5=19 This problem has no solution.
x2 + 2x -6 = 0 x2 + 2x + 1 = 7 (x + 1)2 = 7 x = -1 ± √7
2x + 7 = 1 Therefore, 2x = -6 x = -6/2 x = -3
3X - 1 = 2X + 6 => Bring the 2X to the left X - 1 = 6 => Bring the -1 to the right X = 7
3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3